2015
DOI: 10.1017/s0022149x1500084x
|View full text |Cite
|
Sign up to set email alerts
|

A rare case of cerebral hydatidosis caused by a G1 genotype of Echinococcus granulosus in a cow from Iran

Abstract: Hydatidosis is a medically and veterinary important parasitic disease that is endemic in many parts of the world. Unilocular hydatid cysts may develop in almost any part of the body. Up to 70% of hydatid cysts are located in the liver, followed by 25% in the lungs. Cerebral hydatidosis is an uncommon manifestation of the disease, occurring in less than 1/1000 infected hosts, yet diagnosis does pose a problem. We have reported an exceptionally rare case of cerebral hydatidosis in cattle. This is the first repor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 19 publications
0
2
0
Order By: Relevance
“…Although cattle are considered accidental hosts and infection is generally subclinical, hydatid cysts are frequently found in the viscera at processing 1 , 3 , where they are primarily reported in the liver and lungs 3 , 4 . Cysts are less frequently reported in the heart, kidney, spleen 1 , 3 , 5 and occasionally the brain and skeletal muscle 1 , 6 .…”
Section: Introductionmentioning
confidence: 99%
“…Although cattle are considered accidental hosts and infection is generally subclinical, hydatid cysts are frequently found in the viscera at processing 1 , 3 , where they are primarily reported in the liver and lungs 3 , 4 . Cysts are less frequently reported in the heart, kidney, spleen 1 , 3 , 5 and occasionally the brain and skeletal muscle 1 , 6 .…”
Section: Introductionmentioning
confidence: 99%
“…Although cattle are considered accidental hosts and infection is generally subclinical, hydatid cysts are frequently found in the viscera at processing (Baldock et al, 1985;, where they are primarily reported in the liver and lungs (Banks et al, 2006;. Cysts are less frequently reported in the heart, kidney, spleen (Baldock et al, 1985;Regassa et al, 2010; and occasionally the brain and skeletal muscle (Baldock et al, 1985;Moazeni et al, 2015).…”
Section: Introductionmentioning
confidence: 99%